Floral biology and pollinator activity on parental lines of bottlegourd - SATISH KUMAR; B.S. TOMAR; P.B. SINGH; H. PRASHANTHA BABU; S.N. SINHA (Seed Research, 2026)
A two year experiment was conducted at Indian Agricultural Research Institute, New Delhi to investigate floral biology and honeybee activity on parental lines of bottlegourd, Pusa hybrid-3. The crop was sown in Spring-summer and kharif seasons, with three planting ratios (female: male) 2:1, 3:1 and 4:1. Observations on bee abundance, their foraging modes, time spent per flower, nectar and sugar contents were recorded during both the seasons. Results obtained revealed that Apis mellifera was the most abundant pollinator followed by Apis dorsata, Apis cerana indica and Apis florea. Bee abundance was more in kharif season and honey bee activity was found to be more between 12.00 and 14.00 h in kharif season, whereas in Spring-summer season, it was more at 12.00 and 16.00 h. Pollen gatherers out numbered nectar collectors. Honey bees showed significant difference between movements. Male to male parental line movement was higher than other movements. Apis mellifera spent more time (57.26 sec) per flower followed by Apis dorsata (49.03 sec), Apis cerana indica (40.65 sec) and Apis florea (38.83 sec). The time spent by Apis cerana indica and Apis florea was on par with each other, whereas it had significant difference between Apis mellifera and Apis dorsata. Nectar content (in µl) and Nectar sugar content (in mg) were more in male parental line than in female parental line. Nectar content was higher at 8.00 h, whereas the least nectar content was recorded at 14.00 h. Nectar sugar was the least at 8.00 h and highest at 12.00 and 14.00 h.